Properties of Fresh and Hardened Concrete Containing Supplementary Cementitious Materials State-of-the-Art Report of the RILEM Technical Committee 238-SCM, Working Group 4 (RILEM State-of-the-Art Reports,, 2018)
This volume represents the current knowledge on the effect of SCMs (slag, fly ash, silica fume, limestone powder, metakaolin, natural pozzolans, rice husk ash, special SCMs, ternary blends) on the properties of fresh and hardened concrete (e.g. early strength development, workability, shrinkage) and curing requirements. Other topics treated in the book are postblending vs preblending, implications of SCM variability, interaction between SCM and commonly used admixtures (e.g. superplasticizers, air entrainers).